Mainstreaming occupational safety and health into education : good practice in school and vocational education (Luxembourg, 2004)
"The report is aimed at practitioners and intermediaries within the educational system, and policymakers and social partners both at Member State and EU level. It consists of three main parts: a description of good practice; an analysis of the key elements of a successful mainstreaming process illustrated within a model; and a road map for the future development of a coherent strategy to mainstream occupational safety and health into education at European level. There is a general description of 36 good practice examples from Belgium, Denmark, Germany, Greece, Spain, France, Ireland, Italy, the Netherlands, Austria, Finland, Sweden and the United Kingdom. Of these, 14 examples are presented in detail as case studies. The report covers all stages of education until the end of compulsory education: kindergarten, primary and secondary school, vocational education. As there is such a broad range of examples at different levels, with different organisations initiating the projects and different partners involved, the examples are divided according to three approaches: a ‘holistic’ approach, a curriculum approach and a workplace approach."